Thermal energy storage combined with a temperature boost: An underestimated feature of thermochemical systems. (15th March 2020) - Stengler, Jana; Linder, Marc
Graphical abstract: Operation principle of thermochemical energy storage with combined temperature boost: by increasing the gas pressure before running the exothermic discharging reaction, the stored thermal energy is released at a higher temperature compared to the endothermic charging reaction. Highlights: Experimental study on thermal energy storage combined with heat transformation. Strontium bromide and water vapor as thermochemical working pair. 1 kW thermal power and 100 K temperature boost demonstrated. Temperature lift adjustable from 180 °C to 280 °C by steam pressure variation. Scalable and modular storage design. Abstract: The scientific community largely agrees on both the potential of as well as the need for thermal energy storage (TES) in energy-efficient industrial processes. However, state-of-the-art TES technologies (latent or sensible) have one unsolved issue in common: whenever thermal energy is transferred, e.g. between the heat transfer fluid in an industrial application and the TES, the temperature of the transferred heat decreases. Consequently, even if TES systems perfectly de-couple the temporal correlation between the availability of excess heat, and, e.g., the demand for process heat, the stored heat cannot directly be re-integrated in the same process due to the temperature loss caused by two heat transfers. Here, we report on the development of a thermochemical TES system based on the reversible gas-solid reaction of strontium bromide with water vapor as a reference reaction system. This concept allows for an increase in the temperature of the stored energy without additional process steps, and thereby for a full compensation of the thermal downgrade. The temperature lift is adjustable by variation of the steam pressure, and hence can be adapted to various industrial applications. For example, we charged the storage at 180 °C (1 kPa steam pressure) and discharged it at 280 °C (560 kPa steam pressure), effectively using the module as a heat transformer in addition to the storage function. We present a scalable TES design operating on a 1 kW-scale with 30 min charging and discharging times and an optional temperature boost of up to 100 K.